Efficient and Stable Magnetic Chitosan-Lipase B from Candida Antarctica Bioconjugates in the Enzymatic Kinetic Resolution of Racemic Heteroarylethanols - Cristina Georgiana Spelmezan; László Csaba Bencze; Gabriel Katona; Florin Dan Irimie; Csaba Paizs; Monica Ioana Toșa (Molecules, 2020)
Lipase B from Candida antarctica immobilized by covalent binding on sebacoyl-activated chitosan-coated magnetic nanoparticles proved to be an efficient biocatalyst (49.2–50% conversion in 3–16 h and >96% enantiomeric excess) for the enzymatic kinetic resolution of some racemic heteroarylethanols through transesterification with vinyl acetate. Under optimal conditions (vinyl acetate, n-hexane, 45 °C), the biocatalyst remains active after 10 cycles.